JA:2021-1. Describing the Burden of Injuries in the Cattle Feeding Industry. Issue 3 (2nd July 2020) - Adhikari, Suraj; Rautiainen, Risto; Keenan, Mike; Yoder, Aaron
ABSTRACT: Introduction : Few research projects have addressed health and safety issues in the cattle feeding industry. The Central States Center for Agricultural Safety and Health (CS-CASH) is ideally located to conduct such research, as half of the feedlots in the US are located in the Center's region. CS-CASH has funded several pilot projects addressing the safety and health of livestock workers, and the research team has experience in developing, implementing, and evaluating interventions. In addition, CS-CASH hosted a roundtable discussion of major stakeholders regarding the prevention of injuries and illnesses in the feedlot industry. This project is the first step in investigating and describing the burden of injuries in the cattle feeding industry. Purpose : The long-term goal of this project is to reduce the burden of injuries and illnesses among feedlot workers. Methods : The research team conducted a systematic review of the literature and available sources related to counts, rates, severity, lost time, cost, and indirect consequences of injury and illness. Multiple sources of information were used to quantify the burden of injury and illness in the cattle feeding industry. The burden of injury was evaluated using collected injury incidence and characteristics data. Workers Compensation sources provide data for direct costs: paid benefits and medical expenses. Indirect cost estimation methods were reviewed regarding their applicability to the cattle feeding industry. Results/Findings : Initial findings from 2014 include an occupational fatality rate of 116 fatalities/100, 000 workers in the beef cattle ranching and farming industries (including feedyards). This rate was four times higher than the rate in the agriculture, forestry, and fishing sector overall (24.9/100, 000) and 34 times higher than the rate in all industries combined (3.4/100, 000). The cattle feedyard subsector also has exceptionally high non-fatal injury and illness rates. In 2013, hired workers in the beef cattle ranching and farming (including feedyards) had a "days away from work" rate of 258.8/10, 000 while the rate for all industries combined was 99.9/10, 000. Practical Application : Investigating and describing the burden of injuries in the cattle feeding industry is the first step in developing research and education priorities for that industry. The findings from this study will be used to guide the development of injury mitigation interventions and educational programs for the cattle feeding industry.